2014
DOI: 10.1177/0095798414537935
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Psychological Consequences of Internalized Colonialism on the Psychological Well-Being of Young Adults in Ghana

Abstract: This study examined the psychometric properties of a revised version of the Colonial Mentality Scale in a sample Ghanaian young adults (CMS-G; N = 431). In addition, the degree to which mental health and self-and group-concept was effected by internalized notions of colonial mentality was assessed. Both exploratory and confirmatory factor analyses were used to evaluate the underlying factor structure of the CMS-G. The findings indicated that the CMS-G produced a four-factor orthogonal model as best representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 36 publications
4
48
0
Order By: Relevance
“…A score of 11-20, and scores above 20 represented mild-moderate depression and severe depressive respectively. The CES-D10 has been used extensively in other countries in Sub-Saharan Africa (Othieno et al, 2014;Kilbourne et al, 2002;Peltzer et al, 2013), and had a strong reliability of 0.84 in the Ghanaian context (Utsey et al, 2014). A Cronbach alpha coefficient value of 0.72 was found for this study.…”
Section: Depressive Symptomsmentioning
confidence: 63%
“…A score of 11-20, and scores above 20 represented mild-moderate depression and severe depressive respectively. The CES-D10 has been used extensively in other countries in Sub-Saharan Africa (Othieno et al, 2014;Kilbourne et al, 2002;Peltzer et al, 2013), and had a strong reliability of 0.84 in the Ghanaian context (Utsey et al, 2014). A Cronbach alpha coefficient value of 0.72 was found for this study.…”
Section: Depressive Symptomsmentioning
confidence: 63%
“…It is noteworthy that the first quantitative measure for internalized racism—the Nadanolization Scale—was not published until Taylor and Grundy (), perhaps a reflection of how internalized racism has been neglected by psychology. However, what is perhaps a reflection of the recent surge in psychological interest in internalized racism is that—in just the last decade—there have been psychometrically developed scales to capture internalized racism as experienced by various groups, such as African Americans (Bailey et al., ), Asian Americans (Choi, Israel, & Maeda, ; Liao, ), Filipino Americans (David & Okazaki, ), Latinx (Hipolito‐Delgado, ), Puerto Ricans (Capielo et al., ), Ghanaians (Utsey et al, ), and even a general scale for use with all Peoples of Color (Campon & Carter, ). Although groups differ in their experiences of internalized racism (e.g., desiring straight hair is common among African Americans but not Filipinos, while desiring straighter/bridged noses is common among Filipinos but not African Americans), it is important to note that there are some consistent similarities such as feelings of inferiority, shame, or embarrassment; adopting American or Western standards of physical attractiveness (e.g., lighter skin tones); animosity toward other members of one's racial/ethnic group; and minimizing, tolerating, denying, and even justifying racism.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have also found correlations between internalized racism and higher levels of hopelessness (Cort et al., ) and stress (e.g., Bailey, ; Garcia, David, & Mapaye, ; Grace, ; Szymanski & Obiri, ; Tull, Sheu, Butler, & Cornelious, ). There is also a growing body of empirical literature documenting internalized racism's links with specific psychological disorders like depression (e.g., Cajucom, ; David, , ; David & Okazaki, ; Molina & James, ; Mouzon & McLean, ; Utsey et al., ), anxiety (e.g., Clement, ; Graham, West, Martinez, & Roemer, ; Utsey et al., ), and body dissatisfaction (e.g., Cajucom, ; Cort et al., ; Mason, ). Furthermore, some studies have linked internalized racism to physical ailments such as obesity (e.g., Butler, Tull, Chambers, & Taylor, ; Chambers et al., ; Martin, ), cardiovascular disease (e.g., Chae, Lincoln, Adler, & Syme, ), and even sooner death as internalized racism has also been found to be related to shorter telomere length (i.e., Chae et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we argue that the observation is a narrow, overt manifestation of a general tendency for Asians to be prejudiced and to discriminate in favor of Whites. While a similar phenomenon has been investigated in other countries (David & Okazaki, 2006b;Utsey, Abrams, Opare-Henaku, Bolden, & Williams, 2015), there are little to no experimental investigations of the Pinkerton syndrome in Singapore.…”
mentioning
confidence: 90%